Implementation of Digital Literacy in Islamic Education: Teachers Strategies for Character Building in the Era of Growing Social Media Use - Rahimi, Rahimi; Saputra, Rahmat; Suroto, Suroto; Mohd. Adan, Nur Syakirah Binti (Sekolah Tinggi Agam Islam Sumatera Medan, 2025)
The development of digital technology and the widespread use of social media among teenagers have a significant impact on student behavior and character, including in the madrasah environment. Islamic education is required to be able to respond to this challenge through strengthening digital literacy based on Islamic values. This study aims to analyze the implementation of digital literacy and teacher strategies in shaping student character at MTs. Nurul Falah West Aceh Regency in the era of growing social media. This research uses a qualitative approach with observation, interview, and documentation techniques to explore data in depth. The results showed that digital literacy is integrated in Islamic Religious Education learning through the use of digital media. Teachers' strategies in shaping student character through digital literacy are carried out with an Islamic values-based approach, habituation of digital ethics, and guidance on healthy and responsible use of social media. The challenges faced include limited facilities, low digital literacy, and the negative influence of social media. The implications of the research encourage the need for continuous digital literacy training for teachers and students to strengthen Islamic character in the digital era.